Targeting of lamivudine into the HIV reservoir in mesenteric and peripheral lymph nodes - Wong, Abigail (2024)
Efficient delivery of antiretroviral agents to lymph nodes is important in order to decrease the size of the HIV reservoir within the lymphatic system. Lymph nodes are a major site for HIV replication and are implicated in harbouring latent reservoirs. Lamivudine (3TC) is a nucleoside reverse transcriptase inhibitor (NRTI) used in first-line therapy for the treatment of HIV. Due to its hydrophilicity, 3TC, is not expected to associate with chylomicrons and therefore is predicted to have negligible direct uptake into intestinal lymphatics following oral administration with lipids. Negligible amounts of 3TC are also expected to be transported into peripheral lymphatics following subcutaneous (SC) administration due to faster flow rate in blood capillaries compared to lymph capillaries. The aim of this project was to develop a strategy to deliver 3TC to the HIV reservoir in multiple lymph nodes throughout the body using both oral and SC or transdermal administrations. First, a high performance liquid chromatography with ultraviolet detector (HPLC-UV) bioanalytical method for the detection of 3TC in rat plasma was developed and partially validated. The developed method had a limit of quantification (LOQ) of 15 ng/mL. The calibration curve showed linearity from 15 to 10,000 ng/mL, which was sufficient for the purposes of this study. In addition, this method was designed to be easily modifiable to simultaneously quantify highly lipophilic prodrugs. Next, 3TC was assessed for association with natural and artificial chylomicrons and solubility in sesame oil. As 3TC association with chylomicrons was undetectable, fatty acid ester prodrugs of 3TC were designed using a previously described in silico model with the goal of increased chylomicron association. These prodrugs were then synthesized and assessed for conversion to 3TC in incubated rat plasma and fasted state simulated intestinal fluid (FaSSIF). In addition, the prodrugs (3TC-stearate and 3TC-oleate) were evaluated for association with artificial chylomicrons and solubility in sesame oil. Although both prodrugs had increased association with chylomicrons compared to 3TC, following these assessments, it was determined that neither of the synthesized prodrugs would be good candidates for oral in vivo studies due to low solubility in sesame oil (3TC-stearate) or low stability in FaSSIF (3TC-oleate). Next, pharmacokinetic studies were performed for 3TC in male Sprague-Dawley rats. The biodistributions of 3TC following oral lipid-based, oral lipid-free, SC and intravenous (IV) administrations were assessed using time points determined from the pharmacokinetic studies. In oral administration studies, mesenteric lymph nodes (MLNs) were found to have significantly higher concentrations of 3TC compared to other peripheral lymph nodes with mean tissue:serum ratios for MLNs ranging from 1.4 to 2.9. An analysis of collected mesenteric lymph fluid showed that 3TC is primarily found in the “fluid only” compartment (free of cells and chylomicrons). There were low-to-undetectable concentrations of 3TC in lymph fluid cells and chylomicrons. In SC administration studies, right-side inguinal and popliteal lymph nodes that drain the site of injection were found to have significantly higher concentrations of 3TC than left-side non-draining nodes. The tissue:serum ratios were as high as 3.2 on the right-side inguinal node. In IV administration studies, lymph nodes had tissue:serum ratios ranging from 0.9 to 1.4. Because SC administration biodistribution studies showed high concentrations of 3TC in lymph nodes that drain the site of injection, we then formulated dissolvable 3TC-loaded microneedle (MN) patches. These patches were rigid and were able to be inserted into Parafilm M and pig skin to appropriate depths. Franz cell diffusion studies showed that the microneedle patches successfully delivered 14.5% of the total 3TC in the patch across a matrix of porcine skin into the receptor fluid of phosphate buffered saline (PBS) with an additional 13% of total 3TC being found in the skin. In conjunction with our SC administration biodistribution studies, the in vitro data show that dissolvable 3TC-loaded microneedle patches may be a patient-friendly way to deliver 3TC to peripheral lymph nodes. Using a combined oral and subcutaneous or transdermal administration approach could be a holistic way to deliver 3TC to numerous lymph nodes throughout the body. By doing so, antiretrovirals can be delivered to tissues that harbour HIV latent reservoirs, which could help to improve the prognosis people living with HIV and work synergistically with possible HIV-curative strategies.